A forecast and strategic planning of staffing in geology sector: problems and solutions - V. I. Lisov; E. S. Kushel' (Известия высших учебных заведений: Геология и разведка)
The paper discusses the mam conceptual statements, concerning design of the system of strategic plannin of human resources development in geological sector. The ways of scientific researches in this problem are suggested.